Altered dopamine metabolism and response to treatment with Levodopa/Carbidopa in MCT8 deficiency - Bruschi, Fabio; Vaia, Ylenia; Antonello, Clara E.; Spada, Marco; Porta, Francesco; Marinaccio, Cristina; Carducci, Claudia; Opladen, Thomas; Sartorelli, Jacopo; Zibordi, Federica Maria; Ghezzi, Daniele; Nicita, Francesco; et al. (Movement disorders, 2025)
Background Allan-Herndon-Dudley syndrome (AHDS)/monocarboxylate transporter 8 (MCT8) deficiency is a rare X-linked encephalopathy caused by SLC16A2 variants, impairing thyroid hormone (TH) transport into the brain. This leads to early central nervous system (CNS) TH deficiency, affecting brain maturation. Dopaminergic circuit involvement is suggested by both pathophysiology and clinical features, reminiscent of infantile parkinsonism. Objective This study investigates dopamine metabolism and levodopa/carbidopa response in MCT8 patients. Methods We retrospectively and prospectively collected clinical, genetic, and neuroimaging data, performed cerebrospinal fluid (CSF) biogenic amine analyses, and conducted neurological assessments before and after the levodopa trial (10 mg/kg/day). Results Ten patients exhibited developmental delay, spasticity, and infantile parkinsonism. CSF analysis showed reduced homovanillic acid in 3/10 patients, with 7/10 in the lowest quartile. Levodopa improved parkinsonism and reactivity in 7/10 patients. Conclusions Our findings confirm dopaminergic involvement in AHDS and show that levodopa/carbidopa effectively treats extrapyramidal symptoms. Further investigations could differentiate presynaptic and postsynaptic defects to optimize dopaminergic therapy. © 2025 The Author(s). Movement Disorders published by Wiley Periodicals LLC on behalf of International Parkinson and Movement Disorder Society.